Effect of RNAi down-regulation of three lysine-deficient kafirins on the seed lysine content of sorghum [Sorghum bicolor (L.) Moench] - Kunert, Karl J. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.